Visible light photocatalytic properties of α-Bi2O3 composited with Fe2O3. (July 2014) - Gao, Y.; Xin, H. J.; Shang, J.; Wang, L.; Hao, W. C.; Wang, T. M.
<x content-type="archive" xml:space="preserve">Abstract</x> Bismuth oxide was widely studied as an important metal oxide semiconductor. In this paper, a series of α-Bi2O3/Fe2O3 with different contents of Fe2O3 were synthesised using a sol–gel method. The photocatalytic performance of composites powder was evaluated using rhodamine B (RhB) as a model pollutant under visible light irradiation (λ>420 nm). The α-Bi2O3/Fe2O3(x) samples present much higher photocatalytic performance than that of pure α-Bi2O3. When the composite content is 30 wt-%, the composite shows the best performance which can effectively degrade 85% RhB within 60 min. In addition, the photocatalytic mechanism of this kind of composite photocatalyst was discussed.